2017
DOI: 10.1161/circresaha.116.309948
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive TALEN-Based Knockout Library for Generating Human-Induced Pluripotent Stem Cell–Based Models for Cardiovascular Diseases

Abstract: Rationale Targeted genetic engineering using programmable nucleases such as transcription activator–like effector nucleases (TALENs) is a valuable tool for precise, site-specific genetic modification in the human genome. Objective The emergence of novel technologies such as human induced pluripotent stem cells (iPSCs) and nuclease-mediated genome editing represent a unique opportunity for studying cardiovascular diseases in vitro. Methods and Results By incorporating extensive literature and database searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…50 IPSCs are gradually applied to disease models, drug screening, regenerative medicine, and other fields. 51,52 Führmann et al have reported a peptide-modified, minimally invasive, injectable hydrogel containing hyaluronan and methylcellulose. 53 They used the biomaterial to enhance the survival of human iPSCs-derived oligodendrocyte progenitor cells and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…50 IPSCs are gradually applied to disease models, drug screening, regenerative medicine, and other fields. 51,52 Führmann et al have reported a peptide-modified, minimally invasive, injectable hydrogel containing hyaluronan and methylcellulose. 53 They used the biomaterial to enhance the survival of human iPSCs-derived oligodendrocyte progenitor cells and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this can be achieved with viruses, RNA interference or transgenic approaches to either overexpress or repress the gene or specific variant implicated as being disease causative. Indeed these approaches have all been used to examine the pathogenicity of both channelopathy-and cardiomyopathycausing cardiac variants [66][67][68][69] (see Supplemental Table S1 for complete list). Although the genetically modified hiPSC-CMs exhibited the expected phenotypic changes, as the introduced constructs are heterologously expressed, the resulting lines might not accurately reflect the molecular mechanisms underlying the disease pathology.…”
Section: Improving Hipsc Cvd Models Through Genetic Engineeringmentioning
confidence: 99%
“…TALENs have been used to generate a wide variety of human embryonic stem cell (hESC)-based models to study cardiomyopathies. Karakikes and colleagues (2017) used TALEN constructs to knockout 88 genes associated with cardiomyopathies and congenital heart diseases in hiPSCs [65]. All constructs were validated and found to disrupt the target locus at high frequencies.…”
Section: In Vitro Modelsmentioning
confidence: 99%